(untitled) - Hannam, Joyce (Đồng Nai, 2009)
Pack of ten best-selling Bookworms ideal for building up class libraries. Each Pack contains one copy of each listed title. * The Adventures of Tom Sawyer * The Elephant Man * A Little Princess * Love or Money? * The Monkey's Paw * The Phantom of the Opera * The President's Murderer * Sherlock Holmes and the Duke's Son * White Death * The Wizard of Oz
Keywords: English language,Christmas,Ngôn ngữ tiếng Anh,Giáng sinh; Readers,Người thích đọc sách